Impact of contraception counseling on choice of combined hormonal methods in Colombia (2015)
Objective. Determine the impact of informed contraceptive counseling on choice of contraceptive method. Methods. Multicenter descriptive study using before-and-after evaluation in nine cities in Colombia. Women considering use of self-administered combined hormonal methods at the time of consultation were invited to participate. They were asked about contraceptive method use and preference, following signing of informed consent. Later, they were given standardized medical advice on contraception and then asked again about contraceptive preference and reasons for their choice. Results. The study enrolled 858 women. At the beginning of the study, 538 (62.7%) women were using the combined pill and 281 (32.8%) were not using any contraceptive method. Before receiving counseling, women showed a preference for the pill (62.7%), followed by the intravaginal ring (28.4%), and transdermal patch (14%). After counseling, preferences were as follows: pill (40.8%), intravaginal ring (31.5%), and transdermal patch (11.3%). After counseling, 32.5%, 26.8%, and 7.5% of those considering the pill, patch, and ring, respectively, changed their intended choice. Region of origin, employment status, desire to conceive a child in the future, and having a stable relationship showed a statistical relationship to choice of method. However, age, number of children, and level of education were not determining factors. Conclusions. Medical advice has an impact on choice of self-administered combined hormonal contraceptives, which helps women to use the method of their choice and improves adherence to the method in accordance with its particular conditions.